STUDENTS’ PERCEPTION OF TEACHER’S BILINGUAL LANGUAGE USE IN ENGLISH CLASSROOM (A CASE STUDY AT SMKN 1 WONOSOBO) - Ummi Nadhiroh; Inayah Setyorini (Cahaya Ilmu Bangsa Institute, 2023)
This study aimed to investigate the perception of students toward the use of teacher’s bilingual language in English Classroom and to find out its weakness and benefits for students in English learning. The descriptive qualitative approach was employed in this study. The participants of this study were 36 students, 10 students in 10th grade, 10 students in 11th grade, and 16 students in 12th grade at SMK 1 Wonosobo. A questionnaire that consists of 10 questions was distributed to the students to get primary data. This study reveals that (1) students show their positive perceptions to the use of bilingual language used by the teacher as language instruction in their English classroom; (2) there were two weaknesses of teacher’s bilingual language use for students in learning English; students’ lack in mastering their speaking ability in EFL, students mostly not accustomed to the English language in the class. (3) there are some benefits of teacher’s bilingual language: making them easy to understand what the teacher explained especially some difficult material such as English Grammar, feeling comfortable during the class, easy to understand new vocabularies in English, helping them to do exercises and to read something in English correctly.